2009
DOI: 10.1111/j.1439-0531.2007.01058.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Expression of TIMP‐2, SOD, Vimentin and PAI Proteins in Cloned Bovine Placentae

Abstract: Cloned mammals suffer from high rates of placental abnormality and foetal loss during pregnancy. We previously used 2-D gel electrophoresis and mass spectrometry for global proteomic analysis of cloned and normal bovine placentae to identify differential protein expression patterns. Here, we used Western blot analysis to confirm the expression levels of several pregnancy-related proteins putatively identified as being differentially expressed in somatic cell nuclear transfer (SCNT) vs normal bovine placentae. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
2
10
1
Order By: Relevance
“…This suggests that H3-K9/ K14 histone acetylation may be important for regulation of TIMP-2 and PBEF gene expression in the developing mouse placenta. Thus, our present results support the notion that cloned placentae probably appear to suffer from failed reprogramming of histone modifications in developmentally important genes, leading to aberrant expression of their protein products and changes in TIMP-2 and PBEF expression are likely to be involved in the placental abnormalities seen among cloned mice and cows (e.g., enlargement and/or improper functionality) (8)(9)(10).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This suggests that H3-K9/ K14 histone acetylation may be important for regulation of TIMP-2 and PBEF gene expression in the developing mouse placenta. Thus, our present results support the notion that cloned placentae probably appear to suffer from failed reprogramming of histone modifications in developmentally important genes, leading to aberrant expression of their protein products and changes in TIMP-2 and PBEF expression are likely to be involved in the placental abnormalities seen among cloned mice and cows (e.g., enlargement and/or improper functionality) (8)(9)(10).…”
Section: Discussionsupporting
confidence: 77%
“…Consistent with this hypothesis, recent studies have shown that errors in the epigenetic reprogramming of the somatic cell genome can result in the dysregulated expression of developmentally imprinted genes in cloned embryos, fetuses and placentae, leading to abnormalities in the resulting cloned animals (4)(5)(6). In this context, numerous groups have reported abnormal gene expression patterns related to somatic cell nuclear transfer (7)(8)(9)(10). However, the existence, importance and regulation of abnormal gene expression through epigenetic modification have not yet been fully elucidated in the context of placentation.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…This study also confirmed other studies showing that placentomes from apparently non-pathological clones were over the normal weight range (see EFSA 2009, EFSA 2008. Aberrant gene expression has been reported in the bovine placenta, in a study that analysed placenta from three clones that died immediately after birth (Kim et al, 2009a). In this study placentas from artificial insemination were used as controls instead of placentas from live born clones.…”
Section: Aberrant Gene Expression In Placentamentioning
confidence: 99%
“…Consistent with this hypothesis, errors in the epigenetic reprogramming of the somatic cell genome have been associated with the expressional dysregulation of developmentally imprinted genes in cloned embryos, fetuses and placentae, and abnormalities in the resulting cloned animals [11,12,13,14,15]. In this context, numerous researchers have observed abnormal gene expression patterns following somatic cell nuclear transfer [16,17,18,19]. However, the existence, importance, and regulation of epigenetic modification-related abnormalities in gene expression have not yet been fully elucidated in the context of placentation.…”
Section: Introductionmentioning
confidence: 99%